Positive Mindset Workshop to Increase Work Motivation of Teachers and Education Personnel - Sabriyanti Roose; Rosmala Dewi; Dionisius Sihombing; Yuniarto Mudjisusatyo; Arif Rahman; Aman Simamare-mare; Isli Iriani Indiah Pane (Asia Pacific Journal of Management and Education (APJME), 2025)
This study aims to develop a positive mindset workshop aligned with the work motivation needs of teachers and education personnel, describe its implementation, and analyze its effectiveness. The research employed a Research and Development (RD) approach using the ADDIE model, which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. The participants included 30 teachers and education staff from various schools in North Aceh. The workshop was designed to foster a growth-oriented mindset, self-awareness, and intrinsic motivation among participants through interactive sessions, reflective practices, and collaborative learning. To assess the effectiveness of the workshop, pretest and posttest scores on work motivation were analyzed using the Wilcoxon signed-rank test. The average motivation score increased from 52.43 in the pre-test to 54.27 in the post-test, with an average increase of +1.83 points. Although the increase appears numerically to be moderate, statistical tests show significant significance. Yielded a p-value = 0.00001016 ( 0.05), which means there is a significant difference between the results before and after the training. Thus, training has been proven to have a positive impact on increasing participants' work motivation.